Heat Shock Protein HSP24 Is Involved in the BABA-Induced Resistance to Fungal Pathogen in Postharvest Grapes Underlying an NPR1-Dependent Manner - Li, Chunhong; Cao, Shifeng; Wang, Kaituo; Lei, Changyi; Ji, Nana; Xu, Feng; Jiang, Yongbo; Qiu, Linglan; Zheng, Yonghua (Frontiers in Plant Science, 2021)
Although heat shock proteins (HSPs), a family of ubiquitous molecular chaperones, are well characterized in heat stress-related responses, their function in plant defense remains largely unclear. Here, we report the role of VvHSP24, a class B HSP from Vitis vinifera, in β-aminobutyric acid (BABA)-induced priming defense against the necrotrophic fungus Botrytis cinerea in grapes. Grapes treated with 10 mmol L-1 BABA exhibited transiently increased transcript levels of VvNPR1 and several SA-inducible genes, including PR1, PR2 and PR5. Additionally, phytoalexins accumulated upon inoculation with the gray mold fungus B. cinerea, which coincided with the action of a priming mode implicated in pathogen-driven resistance. Intriguingly, electrophoretic mobility shift (EMSA), yeast two-hybrid (Y2H) and His pull-down assays demonstrated that the nuclear chaperone VvHSP24 cannot modulate the transcript of PR genes but does directly interact with VvNPR1 in vivo or in vitro. Furthermore, we found that VvHSP24 overexpression enhanced the transcript levels of NPR1 and SA-responsive genes (PR1, PR2 and PR5) and increased the resistance of transgenic Arabidopsis thaliana to B. cinerea compared with wildtype Col-0. An opposite trend between CRISPR mutants of AtHSFB1 (the orthologous gene of VvHSP24 in Arabidopsis) and wildtype plants was observed. Hence, our results suggest that VvHSP24 has a potential role in NPR1-dependent plant resistance to fungal pathogen. BABA-induced priming defense in grapes may require posttranslational modification of the chaperone VvHSP24 to activate VvNPR1 transcript, leading to PR gene expressions and resistance phenotypes.